Effects of Lysine on Performance of Lactating Primiparous Sows - K. M. Gourley; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 111 primiparous sows (Line 241; DNA, Columbus, NE) were used in a 21-d study to determine the effect of lysine (Lys) intake during lactation on sow and litter performance and subsequent reproductive performance of primiparous sows. At d 110 of gestation, sows were weighed and randomly assigned to treatment based on weight block. Dietary treatments consisted of increasing levels of standardized ileal digestible (SID) Lys (0.80, 0.95, 1.10, and 1.25% with other AA meeting or exceeding NRC [2012] recommendations as a ratio to Lys). All other nutrients met or exceeded the NRC (2012) estimates. During the lactation period, there were no differences in ADFI or sow BW at d 0 or weaning, resulting in no differences in BW loss. However, backfat loss during lactation decreased (linear, P = 0.046) as SID Lys increased. Regardless of treatment, there were no differences in litter weaning weight or litter gain from d 2 to weaning. In addition, no differences were observed for wean-to-estrus interval or the percentage of females bred by d 7 after weaning. However, d 30 conception rate increased (quadratic, P = 0.042) as Lys increased up to 0.95% SID Lys, but then decreased as SID Lys reached 1.25%. On the subsequent cycle, there was a tendency for decreased (quadratic, P = 0.054) percentage born alive as Lys increased to 0.95% SID; however, percentage born alive increased thereafter. Reciprocally, percentage of mummies tended to increase (quadratic, P = 0.090) with the greatest percentage mummies at 0.95% SID Lys. Overall, this study would suggest that in primiparous sows, there was no effect of increasing SID Lys above 0.80% on sow or litter performance. This study suggests that sow BF loss through lactation was decreased as SID Lys increased; however, little change on reproductive performance was observed. Additional research should be conducted with a larger group of sows housed under commercial conditions to confirm our findings.
Keywords: lactation; lysine; reproduction; sows